2020
DOI: 10.1021/acsapm.0c00480
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Fabrication and Characterization of Pectin Hydrogel Composite Materials for Bone Tissue Repair

Abstract: Development of coatings with tailored surface properties that enhance bone growth is crucial to enhancing the life span of load bearing implants. Bioactive ceramic–polysaccharide hydrogel composite materials are attractive for this application due to their chemical similarity to human bone at the nanoscale. Equally important is the creation of advanced coating processing techniques that can be easily upscaled for mass manufacturing. Toward this aim, we developed an electrochemical fabrication technique for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…47,48 Moreover, these hierarchically structured coatings increased the wettability of the surface, which has also been demonstrated to promote osseointegration. In vitro characterization revealed that these coatings supported both cell proliferation 47,48 and differentiation 48 of osteoblast-like cells. However, a disadvantage of multiscale, hydrophilic surfaces is that they may also promote adhesion and proliferation of bacterial cells.…”
Section: Electrochemical Surface Modificationmentioning
confidence: 96%
See 4 more Smart Citations
“…47,48 Moreover, these hierarchically structured coatings increased the wettability of the surface, which has also been demonstrated to promote osseointegration. In vitro characterization revealed that these coatings supported both cell proliferation 47,48 and differentiation 48 of osteoblast-like cells. However, a disadvantage of multiscale, hydrophilic surfaces is that they may also promote adhesion and proliferation of bacterial cells.…”
Section: Electrochemical Surface Modificationmentioning
confidence: 96%
“…46−48 EPD offers the user a high degree of control over both surface topography and chemistry as well as the ability to deposit uniform films on intricate substrates. 47,48 Coating topography can be altered with ease by varying parameters such as electric field strength, current density, and deposition time. 45 Furthermore, it enables simultaneous deposition of functional macromolecules, inorganic particles, and polymers in a single fabrication step, which circumvents the limitations related to electrochemical anodization.…”
Section: Electrochemical Surface Modificationmentioning
confidence: 99%
See 3 more Smart Citations